2,2,3-Tribromopropanal as a Versatile Reagent in the Skraup-Type Synthesis of 3-Bromoquinolin-6-ols - Lamberth, Clemens; Kessabi, Fiona Murphy; Beaudegnies, Renaud; Quaranta, Laura; Trah, Stephan; Berthon, Guillaume; Cederbaum, Fredrik; Vettiger, Thomas; Prasanna, CS (Synlett, 2014)
2,2,3-Tribromopropanal, a reagent which almost became forgotten in the chemical literature after its first application in the 1950s, is used for the one-step transformation of diversely substituted 4-nitro- and 4-methoxyanilines into 3-bromo-6-nitroquinolines and 3-bromo-6-methoxyquinolines. These intermediates are then converted, in one further step, into 3-bromoquinolin-6-ols, which may carry additional substituents at positions 7 and 8.
Keywords: anilines; quinolone; heterocycle; cyclization; Skraup reaction; kinase inhibitor; fungicide